2014
DOI: 10.1371/journal.pone.0092173
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Antibody-Dependent Enhancement in Vitro Using Viruses and Plasma from Dengue Patients

Abstract: BackgroundThe majority of dengue patients infected with any serotype of dengue virus (DENV) are asymptomatic, but the remainder may develop a wide spectrum of clinical symptoms, ranging from mild dengue fever (DF) to severe dengue hemorrhagic fever (DHF). Severe cases occur more often in patients who experience a secondary infection with a different virus serotype. A phenomenon called antibody-dependent enhancement (ADE) has been proposed to explain the onset of these severe cases, but the exact mechanism of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 43 publications
5
24
1
Order By: Relevance
“…A similar result was found with K562 cells, a second cell line capable of ADE infection. Recently Chaichana and colleagues showed that viruses isolated directly from patient serum were unable to undergo ADE of infection [28], similar to the inability of our low passage isolates to undergo ADE infection.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A similar result was found with K562 cells, a second cell line capable of ADE infection. Recently Chaichana and colleagues showed that viruses isolated directly from patient serum were unable to undergo ADE of infection [28], similar to the inability of our low passage isolates to undergo ADE infection.…”
Section: Discussionsupporting
confidence: 82%
“…2). Similar results showing low ADE infection with DENVs purified directly from patient sera have recently been published [28].…”
Section: Optimization Of Infection: Ade Infectionsupporting
confidence: 85%
“…As with previous studies (Chaichana et al, 2014;Diamond et al, 2000) we found markedly different consequences when infection was undertaken with high and low passage viruses. We found undetectable levels of infection of cells when low passage DENVs were used as the infecting virus.…”
Section: Discussionsupporting
confidence: 81%
“…As several studies have shown that laboratory adapted DENVs can show behavior distinct from that of low passage DENV isolates (Chaichana et al, 2014;Diamond et al, 2000;Edgil et al, 2003), normal control day 7 erythroid committed precursor cells were mock infected or infected with DENV-2 high passage (16681) as used in the previous experiments and a low passage DENV-2 isolate 5, 9, 13), Hb E trait (lanes 2, 6, 10, 14), β-thalassemia trait (lanes 3, 7, 11, 15) and α-thalassemia-1 trait (lanes 4, 8, 12, 16) were either infected (DENV) or mock infected (Mock) on day 7 and day 10 and analyzed after 48 h by western blotting for expression of DENV NS1 and GAPDH in a duplex analysis. (B) Supernatants were collected from day 7 erythroid precursor cells of three normal controls (N1, N2 and N3) at 48 after mock or DENV-2 infection.…”
Section: Erythroid Committed Precursor Cells and Low Passage Denv Isomentioning
confidence: 99%
“…NS1‐specific antibodies are believed to contribute to disease pathogenesis by activating complement and also leading to endothelial dysfunction . Therefore, in order to investigate if DENV‐NS1‐specific antibodies could potentiate the effects of NS1, we used DENV immune sera in ADE experiments as described previously . We found that there was a trend towards DENV immune sera potentiating the effects of NS1 on monocytes and the production of IL‐10 was higher, especially at 48 h (Fig.…”
Section: Resultsmentioning
confidence: 84%